Hemangioma of the Prostate: A Case Report and Literature Review - Fu-Kai, Hsu; Siu-Wan, Hung; Chih-Ying, Wu; Heng-Chieh, Chiang; Kun-Yuan, Chiu (Archives of Clinical and Medical Case Reports, 2017)
Hemangioma of the prostate is extremely rare. Here we described a 69-year-old man who had lower urinary tract symptoms (LUTS) for 5 years, treated as benign prostate hyperplasia (BPH) by Diode laser enucleation. Massive bleeding developed during the procedure with subsequently recurrent urine retention due to blood clot accumulation off and on for the following 3 years. Selective arterial embolization and repeated bladder irrigation failed to control the continuous bleeding, which finally caused obstructive uropathy. Cystoprostatectomy was then performed and the pathological result proved cavernous hemangioma of the prostate.